Presenting clinical and imaging features of patients with clinically amyopathic interstitial lung disease associated with myositis-specific autoantibodies - Tzilas, Vasilios; Tzouvelekis, Argyrios; Sotiropoulou, Vasilina; Panopoulos, Stylianos; Bouros, Evangelos; Avdoula, Eleni; Ryu, Jay H.; Bouros, Demosthenes (Frontiers in Medicine, 2024)
Lung involvement in the context of idiopathic inflammatory myopathies has significant impact on outcome; early and accurate diagnosis is important but can be difficult to achieve. Patients without clinically evident muscle involvement, in particular, pose a significant diagnostic challenge.A computer-assisted search was conducted to identify patients with amyopathic interstitial lung disease associated with the presence of myositis-specific autoantibodies. Medical records and chest imaging studies were reviewed to identify clinical and radiologic features at presentation.Among 35 patients with amyopathic interstitial lung disease associated with myositis-specific autoantibodies, median age was 65 years (range 43 -78) and consisted of 20 women (57%). Prior visit to rheumatology had occurred in 34%. Presenting symptoms consisted of dyspnea (94%), cough (43%), and arthritis (23%). Raynaud phenomenon, "mechanic hands", Gottron papules and inspiratory crackles were present in 23%, 31%, 9% and 74%, respectively. After a detailed history none of the patients reported muscle weakness, while 4 (11%) patients exhibited increased CK levels of which 2 had a concomitant increase in aldolase levels. Median FVC was 79% predicted (range: 49 -135) and median DLco was 50% predicted (range: 17 -103). HRCT pattern was suggestive of an alternative to UIP pattern in 31/33 (94%) patients; most common imaging patterns were NSIP (49%) and NSIP/OP (39%).In patients with NSIP and NSIP/OP pattern, the presence of amyopathic interstitial lung disease associated with myositis-specific autoantibodies should be considered even in the absence of clinical evident myositis.